Efeitos de uma fração polissacarídica sulfatada da alga marinha verde Caulerpa racemosa (FORSSKÅL) j. Agardh na nocicepção e inflamação. - Ribeiro, Natássia Albuquerque (2012)
Marine algae are abundant sources of sulfated polysaccharides with various biological activities thereby altering its biomolecules are great of commercial interest especially in the pharmaceutical and food industries In this study we investigated a sulfated polysaccharide obtained from the green seaweed Caulerpa racemosa (CrII) as to its effects on nociception and inflammation Initially the CrII (1.0 mg/kg, i.v.) was evaluated for toxicity in mice using a repeated dose model (seven days) After the trial period the CrII proved to be nontoxic The antinociceptive activity was evaluated by the writings of abdominal constrictions induced by acetic acid formalin test and hot plate Swiss male mice were treated with CrII (0.01 0.1 and 1.0 mg/kg i.v.) 30 min before receiving pain stimuli (acetic acid 0.8% or 2% formalin) or heat exposure In trials of abdominal constrictions induced by acetic acid and the formalin test CrII significantly reduced the number of abdominal writhing and paw licking time in the second phase of the experiment respectively In relation to thermal stimulation CrII was unable to prolong the reaction time of animals With respect to effects on inflammation CrII (0.01 0.1 and 1.0 mg/kg i.v.) was evaluated for its potential antiinflammatory using Wistar rats We used assays of cell migration into the peritoneal cavity induced by carrageenan (Cg - 700 mg/cavity) paw edema induced by Cg (700 µg/paw) or dextran (300 µg/paw)With respect to cell migration into the peritoneal cavity there was a significant reduction of neutrophils in all groups treated with the CrII In the test paw edema induced by dextran or Cg CrII was also able to significantly reduce the swelling at all doses used The anti-inflammatory effect of CrII was confirmed by reducing the tissue levels of myeloperoxidase in the tissue of the paws Cg groups In addition we performed an enzyme inhibition assay Hemo-oxygenase-1 (HO-1) using the inhibitor ZnPP IX in order to assess whether the anti-inflammatory effect of CrII was related to the expression of this enzyme The results showed that the inhibition of the HO-1 is associated with inhibition of the inflammatory response of CrII In order to assess whether CrII also has pro-inflammatory effect CrII (0.01 0.1 and 1.0 mg/kg i.pl) was injected into the paw of the rats where the result demonstrated a process inflammation only for animals which received the dose of 1.0 mg/kg Therefore the potential mediators that could be involved in the inflammatory process of CrII were evaluated using the test paw edema induced by CrII The results showed that the pro-inflammatory effect of CrII may be related to the release of mediators emanating from the path of cyclooxygenase (COX-2 prostaglandins and thromboxanes) The CrII when used as anti-inflammatory agent was unable to inhibit pro-inflammatory effect in the paw edema test in any of the doses (0.01 0.1 and 1.0 mg/kg i.v.) confirming that its anti-inflammatory effect is related to HO-1.